THE IMPACT OF GAMIFICATION ELEMENTS ON EMPLOYEE ENGAGEMENT AND EMPLOYEE PERFORMANCE IN THE SERVICE SECTOR IN BANGALORE. - Mathew, Elizabeth. P.; Venkatesh, Dr. A. Narasima (The journal of contemporary issues in business and government, 2023)
A startup called Bunchball created a gamified system to increase consumer interaction in the early 2000s, gaining a great deal of attention in the process. This trend was adopted and applied in operational areas around the world. Over the years, gamification has been one of the most prominent developing methods that managers have used to boost employee engagement and performance. How to engage and inspire workers to grow and increase their performance in order to share their expertise has become one of the primary strategic objectives of the firm. This research, underpinned by the Flow theory and Kahn's theory of engagement, examined the effect of gamification on knowledge-sharing habits among users. We conducted an online poll with 150 participants from a major firm that introduced social engagement and performance platforms to facilitate internal knowledge exchange. Our research identified significant drivers of employment motivation (rewards-enjoyment, open-mindedness, and training), which resulted in a greater degree of job engagement and performance expectations. This research yields significant insights for practise and theory.